A phase III trial of tirasemtiv as a potential treatment for amyotrophic lateral sclerosis - Hardiman, Orla (Informa Healthcare, 2019)
Objective: To assess the efficacy of tirasemtiv, a fast skeletal muscle troponin activator, vs. placebo in patients with amyotrophic lateral sclerosis. Methods: VITALITY-ALS (NCT02496767) was a multinational, double-blind, randomized, placebo-controlled clinical trial. Participants tolerating 2 weeks of open-label tirasemtiv (125 mg twice daily) were randomized 3:2:2:2 to placebo or one of three target tirasemtiv dose levels, using an escalating dosage protocol lasting 28 days. The primary outcome measure was changed in slow vital capacity (SVC) at 24 weeks. Secondary endpoints included a change in muscle strength and time to respiratory milestones of disease progression. Results: Of 744 participants, 565 tolerated open-label tirasemtiv and received randomized treatment. By 24 weeks, 23 (12.2%) placebo-treated participants discontinued study treatment vs. 129 (34.2%) randomized to tirasemtiv. SVC declined by 14.4% (95% CI: −16.8, −11.9) in the placebo group and 13.4% (95% CI: −15.3, −11.6) in the tirasemtiv group (p = 0.56). Secondary endpoints did not show significant differences. However, participants who tolerated tirasemtiv at their randomized dose showed a numeric trend toward a dose-related slowing of decline in SVC (p = 0.11). Dizziness, fatigue, nausea, weight loss, and insomnia occurred more frequently on tirasemtiv. Serious adverse events were similar across groups. Conclusions: Tirasemtiv did not alter the decline of SVC or significantly impact secondary outcome measures. Poor tolerability of tirasemtiv may have contributed to this result. However, participants tolerating their intended dose exhibited a trend toward treatment benefit on SVC, suggesting the underlying mechanism of action may still hold promise, as is being tested with a different fast skeletal muscle troponin activator (NCT03160898).
Keywords: Randomized clinical trial; Tirasemtiv; Amyotrophic lateral sclerosis (ALS)